Mencegah HIV & AIDS Sejak Dini Demi Generasi Cemerlang, “SAPE” Safe, Aware, Prevention, and Education - Islami, Vita Hani; Aminah, Aminah; Umaimah, Anisa; Jaizzur, Akhmad (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
HIV and AIDS remain global health issues that have a significant impact on adolescents, who are in a vulnerable phase to engage in risky behaviors. A health promotion activity with the theme "Preventing HIV AIDS Early for a Bright Generation – SAPE (Safe, Aware, Prevention, Education)" was conducted at SMP Negeri 27 Samarinda with the aim of increasing students' knowledge, awareness, and preventive attitudes towards HIV/AIDS. This activity involved 30 students who participated in a seminar using interactive lectures, discussions, leaflet distribution, and pre-test and post-test assessments to measure knowledge improvement. The evaluation results showed an increase in students' knowledge from 53.3% in the "good" category before the seminar to 86.6% after the seminar. In addition, students were introduced to the use of a self-administered HIV test based on the Oral Fluid Test (OFT) as part of education on early detection. This activity proved effective in enhancing adolescents' understanding of HIV/AIDS prevention and promoting healthy behaviors.